To develop or to be abandoned again? Tourism spatial quality assessment of brownfield landscape regeneration: a case study of Xi'an Banpo International Art Park, China - Wei, Xia; Maruthaveeran, Sreetheran; Shahidan, Mohd Fairuz; Sha, Tao (Elsevier, 2025)
Brownfield spatial landscape regeneration is an important direction to cope with urban land use conflicts, and it is an important outdoor tourism carrier that displays the historical characteristics of the city. However, the existing brownfield regeneration space generally suffers from the double dilemma of quality fault and feature dissolution, which leads to the risk of spatial vitality decay and secondary abandonment. This research innovatively constructs a comprehensive evaluation system for the regeneration quality of brownfield landscapes. By integrating fuzzy mathematics and the Analytic Hierarchy Process (FAHP), it breaks through the limitations of traditional single-dimension assessment and, for the first time, incorporates several interdisciplinary indicators, such as spatial resilience, cultural legibility, and industry coupling, into the assessment framework. Taking Xi'an Banpo International Art Park as the empirical object, the research finds that its comprehensive index of regeneration quality is 79.19 (Acceptable), especially in the dimensions of business form (0.84), online and offline information dissemination (0.99, 0.91), and regional cultural self-confidence (1.45), revealing a significant shortcoming. This study calls for the construction of a “culture-technology-governance” triadic theoretical framework and proposes a “spatial gene restoration-industrial entropy regulation-digital brand symbiosis” optimization strategy, which forms a “visitor-community-manager” triadic synergy mechanism and makes up for the inadequacy of the existing brownfield regeneration theory in dynamic adaptation research. This assessment system not only provides a relocatable decision-making tool for urban regeneration but also reveals the non-linear evolution law of industrial heritage tourism space regeneration, which is of theoretical construction value for the establishment of brownfield regeneration assessment standards with Chinese characteristics and provides new ideas for the transformation of industrial heritage in global countries. Management implications: 1.Through the adaptive and innovative FAHP, we constructed a comprehensive evaluation system for the spatial quality of brownfield tourism, quantitatively analyzed multiple driving factors such as physical environment, cultural readability, and industry coupling, and provided new ideas and decision-making tools for urban planning managers.2.Xi'an Banpo International Art Park's advantages include physical, functional, and cultural factors, while its disadvantageous factors focus on emotional and informational factors; managers need to adopt the strategy of "making good use of strengths and compensating for weaknesses": strengthening the extraction of cultural IP symbols and implanting intelligent navigation systems to activate the vitality of the space.3.To address the dynamic complexity of brownfield regeneration, a synergistic optimization path of “culture-technology-governance” is proposed.4.The strategy model proposed in this research is not only applicable to Xi'an Banpo Park but can also be extended to similar industrial heritage brownfield sites: reduce the risk of functional homogenization through “entropy value regulation,” enhance the cultural radiance through “digital brand symbiosis,” and finally realize the sustainable transformation of brownfield sites from “negative urban assets” to “new cultural and tourism landmarks.” ultimately realizing the sustainable transformation of brownfield sites from “negative urban assets” to “new landmarks of culture and tourism.”